Organ Directed Toxicity Of Norfloxacin In A Repeated Dose 28 Day Oral Toxicity Study In Female Rats - R. RASHMI,; K. JAYAKUMAR,; H.D. NARAYANA SWAMY,; M. D. BAYER, (International Journal of Pharma and Bio Sciences, 2012)
Subacute repeated dose 28 day oral toxicity study with norfloxacin was conducted in five groups of Wistar albino female rats. The doses administered orally were Sodium Acetate Buffer (50 mmol/L), pH 4.5 (vehicle control), 380, 1140 and 3800 mg/kg norfloxacin for a period of 28 days. The hematological parameters viz., TEC, Hb, Hct and TLC showed significant decreased level in treated (Group II, III and IV) rats compared to their respective control groups. Similarly biochemical parameters viz., aspartate aminotransferase, alanine aminotransferase, BUN and creatinine showed significant increased level in treated (Group II, III and IV) rats compared to their respective control groups. Satellite high dose group animals showed partial recovery in terms of haematological as well as biochemical parameters after cessation administration of norfloxacin for 14 days. There was a significant decrease in body weight gain in treatment group rats during the study period. However satellite high dose group animals showed partial recovery in body weight gain after the administration of norfloxacin was stopped. Histopathology of rats revealed toxic effect of norfloxacin on liver, kidney, heart, spleen and intestine. Satellite high dose group showed recovery to normalcy in histopathological study.